1990
DOI: 10.1007/bf02277296
|View full text |Cite
|
Sign up to set email alerts
|

Infection byBeauveria bassiana ofLeptinotarsa decemlineata larvae as a consequence of fecal contamination of the integument followingper os inoculation

Abstract: A study of per os inoculated larvae was undertaken to determine if the entomopathogenic fungus, Beauveria bassiana, is able to infect the Colorado potato beetle, Leptinotarsa decemlineata, via the alimentary tract. Surface or per os inoculated larvae which were immediately surface sterilized post inoculation did not succumb to infection, whereas those larvae not sterilized became infected. Histological studies of fed or starved, agnotobiotic (with microbial flora) and axenic larvae revealed that conidia can ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 17 publications
3
16
0
1
Order By: Relevance
“…Moreover, larvae feeding on treated-leaves may acquire infection via the gut. Allee et al (1990) found penetration of B. bassiana conidia through the gut in larvae of CPB after consumption of treated-leaves. Miranpuri and Khachatourians (1991) found abundantly germinated B. bassiana conidia in the gut of the larvae of the mosquito Aedes aegypti after 24-48 h of exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, larvae feeding on treated-leaves may acquire infection via the gut. Allee et al (1990) found penetration of B. bassiana conidia through the gut in larvae of CPB after consumption of treated-leaves. Miranpuri and Khachatourians (1991) found abundantly germinated B. bassiana conidia in the gut of the larvae of the mosquito Aedes aegypti after 24-48 h of exposure.…”
Section: Discussionmentioning
confidence: 98%
“…The results reported by Lewis et al (1996) and Wright and Ramos (2005) might be explained by the common fact that larvae feeding on B. bassiana treated leaves may acquire infection via the gut. Allee et al (1990) found penetration of B. bassiana conidia through the gut in larvae of Colorado potato beetle after consumption of treated leaves. Miranpuri and Khachatourians (1991) found abundantly germinated B. bassiana conidia in the gut of the larvae of the mosquito Aedes aegyptii after 24-48 h of exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Allee et al (1990) reported that the rapid rate of food passage by Leptinotarsa decemlineata conferred protection against gut invasion by ingested B. bassiana conidia. In addition to the rapid passage of conidia, the microorganisms associated with the termite gut have an inhibitory effect on entomopathogenic fungi ; therefore, it is unlikely that entomopathogenic fungi invade the alimentary tract of the termite, but the fate of the ingested conidia remains to be clarified by further research.…”
Section: Discussionmentioning
confidence: 98%